Rhizome Buds Disinfection for Preparation of Red Ginger (Zingiber officinale Roxb. var. rubrum Rosc.) In Vitro Culture - Popy Hartatie Hardjo; Alfian Hendra Krisnawan (Fakultas Farmasi, Universitas Surabaya, 2020)
The success of culture initiation depends on explant surface sterilization techniques. Suitable concentration, combinations, and duration of exposure of sterilizing agents are important to raise in vitro culture successfully. The aim of this work is to obtain the suitable sterilization method for explant buds of red ginger rhizome to get the axenic culture. Four sterilizing agents, fungicide, bactericide, Cefotaxime antibiotic, and NaOCl were tested for sterilization by various concentration and duration of exposure. The results showed that sterilizing agents 200 mg/L Cefotaxime and 100 mg/L Benomyl combined with NaOCl decreased the contamination of explants, and achieved 20% axenic culture.